Mahadeo Govind Ranade - P J Jagirdar; JAGIRDAR (P J) (New Delhi National Book Trust, 2022)
To Commemorate the 75th Years of India's Independence, National Book Trust,India under the Azadi ka Amrit Mahotsav programme has launched new publishing series 'India@75' for young and general readers. The book under this series will reflect the momentous ., yet wonderful journey of India. As a part of the series, books on freedom fighters are being developed. The aim behind publishing such books is to make young readers learn about the sacrifice and struggle of our renowned freedom fighters as well as unsung heroes of pre independence era .
Keywords: Criticising British Administration(1878 to 1881); as highcourt judge